2021
DOI: 10.3390/app112411897
|View full text |Cite
|
Sign up to set email alerts
|

Bert-Based Latent Semantic Analysis (Bert-LSA): A Case Study on Geospatial Data Technology and Application Trend Analysis

Abstract: Geospatial data is an indispensable data resource for research and applications in many fields. The technologies and applications related to geospatial data are constantly advancing and updating, so identifying the technologies and applications among them will help foster and fund further innovation. Through topic analysis, new research hotspots can be discovered by understanding the whole development process of a topic. At present, the main methods to determine topics are peer review and bibliometrics, howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…In [26], expose a new method of topic discovery. The method combines a pre-trained Bert model and a k-means spherical clustering algorithm and applies similarity between documents and topics.…”
Section: Related Workmentioning
confidence: 99%
“…In [26], expose a new method of topic discovery. The method combines a pre-trained Bert model and a k-means spherical clustering algorithm and applies similarity between documents and topics.…”
Section: Related Workmentioning
confidence: 99%
“…The authors of [19,[25][26][27][28][29][30] applied word embedding to discover topics in long and short texts, or they applied clustering algorithms. Hence, in [25,26], the authors showed models based on word embeddings.…”
Section: Related Workmentioning
confidence: 99%
“…Ref. [7] applies BERT word embeddings and a classical clustering algorithm (spherical k-means) to assign documents to topics. The proposal encodes documents as a linear combination of word embeddings and word frequencies in the document.…”
Section: Text Classificationmentioning
confidence: 99%